Various Adsorbents for Water Purification Processes - Wawrzkiewicz, Monika; Wołowicz, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The development of effective treatment methods or the synthesis of new effective adsorbents capable of selective sorption of toxic substances is now of great importance. This reprint contains articles focused on wastewater treatment containing heavy metal ions, and hormones from synthetic and real solutions using different types of adsorbent, such as synthetic ion exchangers, natural and synthetic aluminosilicates, zeolites, magnetic multiwall carbon nanotubes, biosorbents, imprinted polymers, and magnetic adsorbents, as well as cost estimation of activated carbon production from waste nutshells by physical activation could be found.